2017
DOI: 10.1002/ijc.30683
|View full text |Cite
|
Sign up to set email alerts
|

Dietary glycemic and insulin scores and colorectal cancer survival by tumor molecular biomarkers

Abstract: Accumulating evidence suggests that post-diagnostic insulin levels may influence colorectal cancer (CRC) survival. Yet, no previous study has examined CRC survival in relation to a post-diagnostic diet rich in foods that increase post-prandial insulin levels. We hypothesized that glycemic and insulin scores (index or load; derived from food frequency questionnaire data) may be associated with survival from specific CRC subtypes sensitive to the insulin signaling pathway. We prospectively followed 1,160 CRC pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…In this study, however, dietary insulin load and dietary insulin index were both strongly associated with worse patient outcome, suggesting that tumour progression among CRC patients may be influenced by acute postprandial insulin secretion in response to food intake. Our findings are consistent with a recent study using a subset of this population with measured tumour molecular markers ( N =1160), in which the overall HR for CRC-specific mortality was 1.19 (95% CI: 1.02–1.38) for an increase of one standard deviation in dietary insulin index ( Keum et al , 2017 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, however, dietary insulin load and dietary insulin index were both strongly associated with worse patient outcome, suggesting that tumour progression among CRC patients may be influenced by acute postprandial insulin secretion in response to food intake. Our findings are consistent with a recent study using a subset of this population with measured tumour molecular markers ( N =1160), in which the overall HR for CRC-specific mortality was 1.19 (95% CI: 1.02–1.38) for an increase of one standard deviation in dietary insulin index ( Keum et al , 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…Among patients with non-metastatic CRC, elevated levels of plasma C-peptide were associated with an increased risk of CRC-specific mortality ( Wolpin et al , 2009 ). In addition, the association between dietary insulin scores and CRC survival appeared more apparent when CRC is negative for PIK3CA mutation and fatty acid synthase (FASN), two molecular markers linked to the insulin signalling pathway ( Keum et al , 2017 ). A recent study demonstrated that dietary sugar intake increases liver tumour incidence in female mice ( Healy et al , 2016 ), suggesting that a higher dietary insulin index may affect CRC progression by promoting metastasis to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Models were adjusted for age at diagnosis, post-diagnosis body mass index, total energy intake, sex, race, year of diagnosis, cancer stage, grade of tumor differentiation, location of primary tumor within the colon, post-diagnosis physical activity, post-diagnosis pack years of smoking, post-diagnosis regular aspirin use, weight change pre to postdiagnosis, post-diagnosis total alcohol intake, and pre-diagnosis EDIH score cancer prognosis has been inconsistent. Whereas one study found higher risk of colorectal cancer recurrence and death associated with higher glycemic load but not higher glycemic index [34]; another found no association between glycemic load or glycemic index and colorectal cancer survival [35]. Glycemic scores are primarily reflective of the postprandial glucose responses of carbohydrate-containing foods, whereas the EDIH score directly reflects insulin increases induced by components of the dietary pattern that may or may not be contributing to calories (e.g., coffee).…”
Section: Discussionmentioning
confidence: 98%
“…The dietary factors included in this review that might be linked to insulin-related pathways, a Western dietary pattern [ 23 , 42 ], sugar-sweetened beverages [ 23 , 43 ], low coffee consumption [ 25 ], and higher dietary glycemic load [ 45 ] all showed increased mortality risk. Also, a high-insulinogenic diet [ 98 ] has been associated with increased mortality risk. However, these studies were almost all conducted in the same cohort embedded in a trial of adjuvant chemotherapy (CALGB 89803) [ 25 , 42 , 43 , 45 ].…”
Section: Discussionmentioning
confidence: 99%